2003
DOI: 10.1097/00001756-200308260-00001
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking prerogatives of olfactory receptors

Abstract: Olfactory receptors lead lives of exclusivity and privilege, the monarchs of fiefdoms organized solely to carry out their instructions. Each olfactory sensory neuron expresses one allele of one of approximately 1000 olfactory receptor genes. It is thought that olfactory receptor diversity is critical for the ability of animals to detect many thousands of odorants, but supporting functional evidence has been difficult to obtain because olfactory receptors expressed in heterologous cells are typically retained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 79 publications
0
52
0
Order By: Relevance
“…It is believed that the major reason for the inefficient expression of ORs in HEK293 cells is the fact that they are retained in the endoplasmic reticulum and cannot reach the cell surface (10,11). Therefore, accessory proteins that help ORs to overcome this problem would be necessary to enable functional OR expression in heterologous cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the major reason for the inefficient expression of ORs in HEK293 cells is the fact that they are retained in the endoplasmic reticulum and cannot reach the cell surface (10,11). Therefore, accessory proteins that help ORs to overcome this problem would be necessary to enable functional OR expression in heterologous cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, so far only Ϸ30 ORs have been linked to odorants they recognized (6)(7)(8)(9). The major reason for this fact is that the functional expression of ORs in heterologous cell types has proven difficult, mostly because ORs cannot reach the plasma membrane (10)(11)(12). To circumvent this problem, we previously used a combination of Ca 2ϩ imaging and single-cell RT-PCR to identify the ORs expressed by olfactory neurons that responded to different aliphatic odorants (6).…”
mentioning
confidence: 99%
“…If one of the subunits is missing this specific interaction is no longer possible. Recently, a checkpoint protein (UNC-101) was identified that controls trafficking of odorant receptors into the olfactory cilia of Caenorhabditis elegans (47,48). Similar proteins may have evolved to control ciliary CNG channel targeting.…”
Section: Cngb1mentioning
confidence: 99%
“…Functional expression of ORs in heterologous cells is, therefore, an important approach for elucidating the molecular mechanism of olfaction and helps to identify specific ligands for particular receptors. Unfortunately, ORs express very inefficiently at the plasma membrane of heterologous cells, apparently because of OR retention in intracellular compartments and degradation via the ubiquitin-proteasome pathway (8)(9)(10). However, direct monitoring of these processes in vivo is still immature.…”
mentioning
confidence: 99%